IMMUNE ASSOCIATED SYNDROMES - P.F. Litvitsky (Вопросы современной педиатрии)
The present publication is the second in a series of the brief lectures dedicated to the characteristics of the system of the immunobiological control over the individual and continuous antigenic contents of the body, as well as immune-associated syndromes most recurrent among people: allergies, immunodeficiency states, pathological tolerance, and immune self aggression diseases. In the first lecture, the author analyzes the modern data on the structure and functions of the immunobiological supervision system. Below is the overview of etiology, pathogeny and principles of therapy for the allergic responses and states.Key words: allergy, allergy transmitters, cytokines, membrane attack complex, hyposensitization.